2008
DOI: 10.1063/1.2831034
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a multi-keV x-ray source produced by nanosecond laser irradiation of a solid target: The influence of laser focus spot and target thickness

Abstract: The influence of focus spot and target thickness on multi-keV x-ray sources generated by 2ns duration laser heated solid targets are investigated on the Shenguang II laser facility. In the case of thick-foil targets, the experimental data and theoretical analysis show that the emission volume of the x-ray sources is sensitive to the laser focus spot and proportional to the 3 power of the focus spot size. The steady x-ray flux is proportional to the 5∕3 power of the focus spot size of the given laser beam in ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Most of the articles concerning this issue concentrate on the influence of the laser intensity (Mattews et al, 1983;Workman et al, 2003;Workman & Kyrala, 2001a, 2001bRiley et al, 2002b;Dunn et al, 1995;Kodama et al, 1986), the atomic number (Kauffman, 1991;Mattews et al, 1983;Workman & Kyrala, 2001a, 2001bDunn et al, 1995;Ruggles et al, 2003;Yaakobi et al, 1981;Kodama et al, 1986), and the initial density of the target (Back et al, 2001(Back et al, , 2003Fiedorowicz, 2005;Fournier et al, 2004Fournier et al, , 2006Kodama et al, 1987;Teubner et al, 1991;Pelletier et al, 1997;Girard et al, 2005Girard et al, , 2004Primout, 2005). We also found that by using a long pulse laser, the laser focus spot size and the thickness of the thinfoil target (the thickness is comparable to the burn through length, which is the initial target thickness that the laser beam can transmit through the entire plasma region with little absorption at the end of the laser pulse) can change the conversion of multi-keV K-shell X-ray emission significantly (Hu et al, 2007(Hu et al, , 2008. We also found that by using a long pulse laser, the laser focus spot size and the thickness of the thinfoil target (the thickness is comparable to the burn through length, which is the initial target thickness that the laser beam can transmit through the entire plasma region with little absorption at the end of the laser pulse) can change the conversion of multi-keV K-shell X-ray emission significantly (Hu et al, 2007(Hu et al, , 2008.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Most of the articles concerning this issue concentrate on the influence of the laser intensity (Mattews et al, 1983;Workman et al, 2003;Workman & Kyrala, 2001a, 2001bRiley et al, 2002b;Dunn et al, 1995;Kodama et al, 1986), the atomic number (Kauffman, 1991;Mattews et al, 1983;Workman & Kyrala, 2001a, 2001bDunn et al, 1995;Ruggles et al, 2003;Yaakobi et al, 1981;Kodama et al, 1986), and the initial density of the target (Back et al, 2001(Back et al, , 2003Fiedorowicz, 2005;Fournier et al, 2004Fournier et al, , 2006Kodama et al, 1987;Teubner et al, 1991;Pelletier et al, 1997;Girard et al, 2005Girard et al, , 2004Primout, 2005). We also found that by using a long pulse laser, the laser focus spot size and the thickness of the thinfoil target (the thickness is comparable to the burn through length, which is the initial target thickness that the laser beam can transmit through the entire plasma region with little absorption at the end of the laser pulse) can change the conversion of multi-keV K-shell X-ray emission significantly (Hu et al, 2007(Hu et al, , 2008. We also found that by using a long pulse laser, the laser focus spot size and the thickness of the thinfoil target (the thickness is comparable to the burn through length, which is the initial target thickness that the laser beam can transmit through the entire plasma region with little absorption at the end of the laser pulse) can change the conversion of multi-keV K-shell X-ray emission significantly (Hu et al, 2007(Hu et al, , 2008.…”
Section: Introductionmentioning
confidence: 84%
“…The detailed characteristics of multi-keV X-ray emission are important to optimize X-ray sources or design experiments. Some papers pay attention to the influence of the laser focus spot size (Mattews et al, 1983;Workman et al, 2003;Workman & Kyrala, 2001a, 2001bRiley et al, 2002b), the laser wavelength (Kauffman, 1991;Hu et al, 2008;Mattews et al, 1983;Yaakobi et al, 1981;Kodama et al, 1986), the laser incidence angle (Mattews et al, 1983), or the laser pulse duration (Mattews et al, 1983;Workman & Kyrala, 2001a, 2001bRiley et al, 2002b;Dunn et al, 1995;Phillion & Hailey, 1986;Kodama et al, 1987;Teubner et al, 1991;Pelletier et al, 1997;Girard et al, 2004;Eidmann & Schwanda, 1991;Limpouch et al, 2002;Von Der Linde et al, 2001), etc. Some papers pay attention to the influence of the laser focus spot size (Mattews et al, 1983;Workman et al, 2003;Workman & Kyrala, 2001a, 2001bRiley et al, 2002b), the laser wavelength (Kauffman, 1991;Hu et al, 2008;Mattews et al, 1983;Yaakobi et al, 1981;Kodama et al, 1986), the laser incidence angle (Mattews et al, 1983), or the laser pulse duration (Mattews et al, 1983;Workman & Kyrala, 2001a…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The large size of the backlighter with 120 m ͑full width at half maximum͒ in diameter slightly lower than the spectral resolution, but can satisfy the requirement for enough backlighting intensity. 20 The pulse width of the x-ray backlighter is about 200 ps. It can provide short enough pulse for time-resolving measurement.…”
Section: Resultsmentioning
confidence: 99%
“…18 Recently the additional ͑ninth͒ laser beam, which can also deliver 70-150 ps short pulse besides the nanosecond long pulse, was established on the Shenguang II laser facility. [19][20][21] The ninth laser beam could be used to generate shorter backlighter compared with the previous experiments. 7,[14][15][16][17] The shorter backlighter could provide better temporal resolution.…”
Section: Introductionmentioning
confidence: 98%